Analysis of Urban Air Pollution and The Effectiveness of Air Pollution Control Policy in Malaysia: Case Study in Klang Valley, Malaysia - Siti Haslina Mohd Shafie; Suzani Mohamad; Nor Lita Fadilah Rameli; Sahala Benny Pasaribu (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
Air pollution in Malaysia is largely attributed to motor vehicles and land transportation, industrial activities and open burning. It has a hazardous effect on the public’s health and the environment. This study focuses on the spatial analysis of carbon monoxide (CO) and ozone (O3) concentrations trend in Klang Valley stations, specifically in Klang, Petaling Jaya, Kajang, Shah Alam and Cheras from 2000 to 2009. The study used the Inverse Distance Weighted (IDW) interpolation technique under the Geographic Information System (GIS). This study found that the distribution pattern of CO spatial concentrations in the Klang Valley is the highest concentration and reached 2.5 ppm, especially in Klang and Petaling Jaya stations in 2002 and 2003. However, the annual concentration of O3 recorded in Klang, Petaling Jaya, Kajang, Shah Alam, and Cheras stations from 2004 to 2009 is between 0.01 to 0.025 ppm. While air quality legislations have been introduced in Malaysia, policies and regulations being established by the government, their enforcement is still weak. Subsequently, air pollution is still a significant issue in Malaysia. Strong cooperation between the government, stakeholders and the local community is important to promote environmental sustainability and improve the community’s well-being.Keywords: Air pollution; Geographic Information System (GIS); Air Quality Policy; Malaysia Analisis Polusi Udara Perkotaan dan Efektivitas Kebijakan Pengendalian Polusi Udara di Malaysia: Studi Kasus di Lembah Klang, Malaysia AbstrakPolusi udara di Malaysia sebagian besar disebabkan oleh kendaraan bermotor dan transportasi darat, kegiatan industri dan pembakaran terbuka. Ini memiliki efek berbahaya pada kesehatan publik dan lingkungan. Penelitian ini berfokus pada analisis spasial trend konsentrasi karbon monoksida (CO) dan ozon (O3) di stasiun Klang Valley, tepatnya di Klang, Petaling Jaya, Kajang, Shah Alam dan Cheras dari tahun 2000 sampai 2009. Penelitian menggunakan Inverse Distance Weighted (IDW) teknik interpolasi di bawah Sistem Informasi Geografis (SIG). Penelitian ini menemukan bahwa pola sebaran konsentrasi spasial CO di Lembah Klang merupakan konsentrasi tertinggi dan mencapai 2,5 ppm terutama di stasiun Klang dan Petaling Jaya pada tahun 2002 dan 2003. Namun demikian, konsentrasi O3 tahunan tercatat di Klang, Petaling Jaya, Stasiun Kajang, Shah Alam, dan Cheras dari 2004 hingga 2009 berkisar antara 0,01 hingga 0,025 ppm. Meskipun undang-undang kualitas udara telah diperkenalkan di Malaysia, kebijakan dan peraturan ditetapkan oleh pemerintah, penegakannya masih lemah. Selanjutnya polusi udara masih menjadi masalah yang signifikan di Malaysia. Kerja sama yang kuat antara pemerintah, pemangku kepentingan, dan masyarakat lokal penting untuk mendorong kelestarian lingkungan dan meningkatkan kesejahteraan masyarakat.Kata Kunci: Polusi udara; Sistem Informasi Geografis (SIG); Kebijakan Kualitas Udara; Malaysia Анализ загрязнения воздуха в городах и эффективности политики контроля за загрязнением воздуха в Малайзии: тематическое исследование в Лембах Кланг, Малайзия АннотацияЗагрязнение воздуха в Малайзии в значительной степени связано с автотранспортом и наземным транспортом, промышленной деятельностью и открытым сжиганием. Это опасно для здоровья населения и окружающей среды. В этом исследовании основное внимание уделяется пространственному анализу тенденции концентраций окиси углерода (CO) и озона (O 3 ) на станции Klang Valley, особенно в Кланге, Петалинг-Джая, Каджанге, Шах-Аламе и Черасе с 2000 по 2009 г. Данное исследование применяет Сглаживание с Весом обратно Пропорциональным Расстоянию (IDW), метода интерполяции в Географической Информационной Системе (ГИС). Это исследование показало, что характер распределения пространственных концентраций CO в Лембах Кланг является наивысшим и достигал 2,5 частей на миллион (2,5 ppm), особенно на станциях Кланг и Петалинг-Джая в 2002 и 2003 годах. Однако годовая концентрация O3, зарегистрированная на станциях Кланг, Петалинг-Джая, Каджанг, Шах-Алам и Черас с 2004 по 2009 год, составляет от 0,01 до 0,025 частей на миллион (2,5 ppm). Несмотря на то, что в Малайзии были приняты законы о качестве воздуха, политика и постановления устанавливаются правительством, их соблюдение все еще остается слабым. Следовательно, загрязнение воздуха по-прежнему остается серьезной проблемой в Малайзии. Тесное сотрудничество между правительством, заинтересованными сторонами и местным сообществом важно для обеспечения экологической устойчивости и улучшения благосостояния сообщества. Ключевые слова: Загрязнение воздуха; Географическая Информационная Система (ГИС); Политика качества воздуха; Малайзия